Roadside Environmental Quality Estimations for Particulate Matter 10 (PM10) in Akure-South LGA, Ondo State, Nigeria - Femi, Odesanya Joseph (Program Pascasarjana Universitas Sriwijaya, 2024)
Transportation serves as a vibrant sector for current civilization without which commerce, industrialization and societal development will be slowed or impossible, however, movement in space is not without its negative outcome, part of which is the generations of particulate. Objective of this research is to analyses Particulate Matter 10 (PM10) on roadside in Akure-south LGA of Ondo State, Nigeria. Traffic movement were collected along these corridors with the aid of counting and then disaggregating them into various categories such as passenger cars, heavy trucks, motorcycles and buses, while, CLJ-D Particulate counter (100-1million (PCS) Brand) was used in collecting PM10 particles generated along the traffic corridor. Finding show that the highest PM10 generated along the corridor is 1019 µg/m3 and the least generated PM10 is 312 µg/m3, while the corridor with the highest traffic is with 3973 pcu/hr and the lest has 1299 pcu/hr traffic volume. The research concluded that although the traffic volume is not exclusively the only contributor to PM10, in the selected corridor, there could also be some other contributors as the areas generating highest traffic movement do not mean highest PM10.